Applicazioni comuni di reologia dei polimeri: Parte I: fluidi non-Newtoniani - Villani, Vincenzo (Chimica nella Scuola, 2023)
Rheology is a highly interdisciplinary approach, transversal to all natural sciences and technologies. Chemistry plays a fundamental role in it, in fact the models at the molecular level are the interpretative key of the experimental data. The mathematics and physics used can be very sophisticated, however using only the fundamental elements of mathematical analysis (supplied to the last years of secondary schools) and the fundamental concepts of structure and molecular interactions it is possible to develop a coherent and rigorous framework. It is certainly useful to the teachers and students of chemistry and, more generally, of natural sciences.